The Role of Chinese Ethnic in Spread of Islam in Indonesia - Fatquri Bin Buseri (Proceeding Of The International Seminar and Conference on Global Issues, 2015)
Islam as a religion in the world also has experienced the spread of up to China, recorded at the time of Caliph Uthman ibn Affan (651 M) commissioned Saad ibn Waqos to spread Islam through the Emperor Yong Hui diplomaasi in Guangzhou. Emperor Yong Hui permits the spread of Islam in China, so since the 7th century Islam has growed up in China. This is evidenced by the presence of the relics Huai Sheng Mosque of Guangzhou. Initially the spread of Islam in Indonesia is not a plan of the Ming Dynasty, the Ming Dynasty as the main objective is to conduct diplomacy with the countries of Asia and Africa. In carrying out diplomatic mission trip Ming Dynasty, led by Admiral Zheng He, always stopped in Indonesia up to 7 times, this is due to the geographical location of Indonesia is very strategic. In the 13th century, the condition of Indonesia as the world shipping transit lanes already crowded by merchants of various countries, this was made the Admiral Zheng He became interested in conducting diplomacy with the Majapahit Empire. Results of diplomacy with the Majapahit Empire was causing the acculturation, because at the time most of Indonesian population is Hindu and Buddhist. Acculturation which held by Zheng He in creating Muslim community of Chinese ethnic and providing agricultural education and carpentry by incorporating elements of religion as the way of spreading Islam. Key words: Role,  Chinese ethnic, Spread of Islam.